Kebijakan Fiskal dalam Perspektif Islam - Pandapotan Ritonga; M. Shabri Abd. Majid (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2023)
In order for Indonesia's 2045 vision to become a sovereign, developed, just and prosperous country, the direction of fiscal policy must be shaped to reflect the dynamics of the economy, respond to challenges and always support sustainability. Therefore, the development of the State Budget as a tool for fiscal policy must be encouraged so that it is healthier in the long run and is able to manage risks so that the allocation, distribution and stabilization functions can be optimized. Of course, the country's economic policy is expected to be in accordance with Islamic principles and values, because the main goal of Islam is the welfare of all mankind. The purpose of this study is to find out how tax policy creates a society based on a balanced distribution of wealth by balancing material and spiritual values. This study uses descriptive methods, data collection techniques are carried out using library technology or other written documents as well as journals, books and other literature. The results of the study show that fiscal policy is a policy that regulates government revenues and expenditures to ensure stability and encourage economic growth. The tools of fiscal policy are government revenues and expenditures. Understanding the Islamic perspective on government spending must be acknowledged. First, government spending can be divided into current spending and capital spending. Second, the objectives of government tax and spending policies are reflected in the redistribution of income, spending on the provision of public services, the production of public goods that cannot be provided by the market, and the provision of infrastructure to increase economic productivity. With all control systems, the advantages of each system must be considered and combined. In a sense, modern taxation accepts ethical ideas and Islamic taxation accepts modern tax theory and applications.